Policiamento comunitário e educação: discursos de produção de uma "nova polícia" - Barboza, Anderson Duarte (2013)
Through analytical tools bequeathed by Michel Foucault, the study aims to investigate the changes in the Police, particularly with the adoption of the Community Policing Doctrine, which became widespread in Brazil in the 1980’s, in which a variety of discourses was used, especially the education, as a way to justify the actions of the Communitarian policeman, now seen as a cop-educator. Analyzing such doctrine, it is realized that, although the progressive perspectives that the term “communitary” confers to it, it has been articulated by a neoliberal governmentality, using the form of large private company as a management model to the Police Corporation and, finally, establishing a entrepreneurship culture among the policemen. All this resulting in greater control and governance of the population.